2005
DOI: 10.1007/s00198-005-2018-x
|View full text |Cite
|
Sign up to set email alerts
|

A list of device-specific thresholds for the clinical interpretation of peripheral x-ray absorptiometry examinations

Abstract: The UK National Osteoporosis Society (NOS) has recently issued new guidelines on the use of peripheral x-ray absorptiometry (pDXA) devices in managing osteoporosis. The NOS guidelines recommend a triage approach in which patients' bone mineral density (BMD) measurements are interpreted using upper and lower thresholds specific to each type of pDXA device. The thresholds are defined so that patients with osteoporosis at the hip or spine are identified with 90% sensitivity and 90% specificity. Patients with a pD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 28 publications
2
39
0
5
Order By: Relevance
“…3 When using the portable Calscan device for OP screening, an upper and a lower triage threshold is applied, which classifies the study population into a group that in all probability has OP, a group that is unlikely to have OP and a group about which there is uncertainty and requires further analysis. 4 This procedure, in which the screened population is divided into three groups, allows an individual with OP in the hip or spine to be identified with 90% sensitivity and 90% specificity. 4 Because OP is such a widespread problem, there is an ongoing discussion of the benefit of a preventative screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 When using the portable Calscan device for OP screening, an upper and a lower triage threshold is applied, which classifies the study population into a group that in all probability has OP, a group that is unlikely to have OP and a group about which there is uncertainty and requires further analysis. 4 This procedure, in which the screened population is divided into three groups, allows an individual with OP in the hip or spine to be identified with 90% sensitivity and 90% specificity. 4 Because OP is such a widespread problem, there is an ongoing discussion of the benefit of a preventative screening.…”
Section: Introductionmentioning
confidence: 99%
“…4 This procedure, in which the screened population is divided into three groups, allows an individual with OP in the hip or spine to be identified with 90% sensitivity and 90% specificity. 4 Because OP is such a widespread problem, there is an ongoing discussion of the benefit of a preventative screening. OP affects all of the bones in the human body, including the mandible.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of axial DXA, current guidelines recommend using peripheral measurements from the hand, forearm or heel to aid in treatment decisions in those with clearly identified clinical risk factors and can be used safely in population screening for osteoporosis (23,24). The UK National Osteoporosis Society suggested that peripheral devices (such as the phalangeal RA device that we used) Bakan be adopted in a triage role (23)(24)(25). A variety of devices are available for assessing sites in the peripheral skeleton, such as the hand, forearm or heel (25).…”
Section: Discussionmentioning
confidence: 99%
“…The UK National Osteoporosis Society suggested that peripheral devices (such as the phalangeal RA device that we used) Bakan be adopted in a triage role (23)(24)(25). A variety of devices are available for assessing sites in the peripheral skeleton, such as the hand, forearm or heel (25). The phalangeal RA device that we used measured phalangeal BMD from the second phalanges of the middle three digits, which made it suitable for use in this study and other studies of screening for osteoporosis (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation